Contemporary challenges in the work of court probation officer for adults. Critical recognition from the perspective of the Polish experience - Kwieciński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper focuses on the issue of probation officer participation in the supervision exercised over offenders exhibiting mental health dysfunctions. The analysis included in the paper applies to both currently applicable law and the proposed legislative solutions. The author’s critical remarks also include proposals de lege lata and de lege ferenda.
Keywords: kurator sądowy; nadzór; zaburzenia psychiczne; zmiany w prawie